How does Yoga Exercise affect Anxiety in Pregnant Women? : Pre-Experimental Study - Mamah Suhaeriah; Linda K Telaumbanua; Nurmah; Astrid F Sianipar (SABDA EDU PRESS (SEP), 2024)
Anxious during pregnancy not only impacts pregnant women's health, but it may also interfere with the delivery process, resulting in early labor, extended labor, cesarean delivery, and low birth weight. According to WHO estimates, psychiatric illnesses affect around 10% of pregnant women and 13% of postpartum women globally. This frequency is greater in underdeveloped nations among pregnant women (15.6%) and postpartum women (19.8%). The goal of this study is to determine the effect of prenatal yoga exercise on the anxiety of pregnant women at TPMB Mamah Suhaeriah in 2022. Method for doing research This sort of study employs the Pre-Experimental technique, using a one-group pretest-posttest design. Total sampling was used, and there were 20 responders in total. An observation sheet was employed as the study instrument. The Wilcoxon Sign Rank Test was performed to analyze the data. The Wilcoxon Sign Rank test yielded a p-value of 0.000, which is less than the threshold of 0.05. This indicates that Ha is accepted. Conclusion: Prenatal yoga practice has an influence on pregnant women's anxiety levels at TPMB Mamah Suhaeriah in 2022. Pregnant women are advised to manage their psychological condition effectively and to exercise often, since exercise has good benefits for survival during pregnancy